Perancangan Game Edukasi Matematika Berbasis Android untuk Siswa Sekolah Dasar Menggunakan Metode GDLC - M. Ziad Mubarok; Anugerah Bagus Wijaya; Banu Dwi Putranto (LPPM Universitas Mulia, 2026)
This study aims to design and develop an Android-based educational mathematics game as an interactive learning medium for elementary school students using the Game Development Life Cycle (GDLC) method. The game adopts an educational monopoly concept integrated with basic arithmetic learning materials, including addition, subtraction, multiplication, and division. The development process consists of the planning, design, development, testing, and implementation stages. The game was developed using the Unity Engine and designed by integrating educational monopoly gameplay with interactive features such as dice rolling, character movement, and reward–punishment mechanisms to create a more engaging and enjoyable learning experience for elementary school students. Black-box testing showed that all game features functioned properly without any functional errors. User testing involving 17 elementary school students and one mathematics teacher resulted in an average feasibility score of 78.8%, which falls into the